If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -50 + 5y + 5 = 3(4y + -3) + -8 Reorder the terms: -50 + 5 + 5y = 3(4y + -3) + -8 Combine like terms: -50 + 5 = -45 -45 + 5y = 3(4y + -3) + -8 Reorder the terms: -45 + 5y = 3(-3 + 4y) + -8 -45 + 5y = (-3 * 3 + 4y * 3) + -8 -45 + 5y = (-9 + 12y) + -8 Reorder the terms: -45 + 5y = -9 + -8 + 12y Combine like terms: -9 + -8 = -17 -45 + 5y = -17 + 12y Solving -45 + 5y = -17 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -45 + 5y + -12y = -17 + 12y + -12y Combine like terms: 5y + -12y = -7y -45 + -7y = -17 + 12y + -12y Combine like terms: 12y + -12y = 0 -45 + -7y = -17 + 0 -45 + -7y = -17 Add '45' to each side of the equation. -45 + 45 + -7y = -17 + 45 Combine like terms: -45 + 45 = 0 0 + -7y = -17 + 45 -7y = -17 + 45 Combine like terms: -17 + 45 = 28 -7y = 28 Divide each side by '-7'. y = -4 Simplifying y = -4
| 3(c-4)+5=2+c-9 | | 14(4x-2)=3x-6 | | 4-4x=10+2x | | 7-(-y-5)=2(y+3)-6(y+3) | | x+x+475000=625000000 | | (3+5x)(2-3x)=12-15x^2 | | -2(-3x+5)+6=4(x-2) | | (3xy-5y^2)(-4x)= | | s+w+2=304 | | (13w+10)-(2w+6)= | | w+s=304 | | 8(w-5)=-40 | | (3x+6)(6x-3)=0 | | 2x^2+12x+8=0 | | 6-3t=3t | | X^2+86x=0 | | (1-7xy+5x^2-y^2)-(6y^2-7xy-6)= | | -(8y+3)-(-7y-6)=-3 | | x^2-8x+5=y | | x^2-8x+5=x | | -(8y+3)-(7y-6)=-3 | | 4(3z-1)-3(2+6)=5(z+1) | | 12-3x+7x=-2(-5x+6) | | n^2-4x-21=0 | | 77=(4+w)(w) | | 5+14t-1=8t+14-4t | | 77=(4w)*(w) | | 0.4(x+0.7)=0.6(x-42) | | 7+16x-4=8x+102-3x | | 5x(4)=16 | | 5x(4)=15 | | x^2=5x+15 |